Pengaruh Celebrity Endorsers, Brand Image, dan Brand Trust Terhadap Keputusan Pembelian Kosmetik Wardah di Denpasar - Ni Luh Putu Diah Anggun Saraswati (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Purchase decisions are crucial to enhance as they represent actions taken by consumers to buy a product. The objective of this study is to investigate the influence of celebrity endorser, brand image, and brand trust on purchase decisions for Wardah products in Denpasar City. The research used non-probability sampling and distributed a questionnaire via Google Forms to 100 respondents. Data were analyzed using SPSS version 26. Findings indicate that celebrity endorser has a positive and significant impact on purchase decisions, brand image also has a positive and significant influence on purchase decisions, and brand trust similarly affects purchase decisions positively and significantly. This study contributes theoretically to different research domains and provides practical insights for cosmetic businesses, particularly Wardah in Denpasar City.